Comparing the techniques and outcomes of laparoscopic transverse colectomy to laparoscopic hemicolectomy in mid-transverse colon cancer resection - Sun, Rui; Zhang, Guannan; Sun, Xiyu; Niu, Beizhan; Zhou, Jiaolin; Cong, Lin; Qiu, Huizhong; Lin, Guole; Wu, Bin; Xiao, Yi (Frontiers in Surgery, 2023)
Introduction: The mid-transverse colon cancer is relatively uncommon in all colon cancers and the optimal surgical approach of mid-transverse colon cancer remains debatable. Aim and Objectives: Our study aimed to depict the techniques and outcomes of laparoscopic transverse colectomy in one single clinical center and compare this surgical approach to traditional laparoscopic right hemicolectomy and laparoscopic left hemicolectomy. Method: This was a retrospective cohort study of patients with mid-transverse colon cancer in one single clinical center from February 2012 to October 2020. The enrolled patients were divided into two groups undergoing laparoscopic transverse colectomy and laparoscopic right/left hemicolectomy, respectively. The intraoperative, postoperative complications, oncological outcomes and functional outcomes were compared between the two groups. The primary endpoint was disease free survival (DFS). Results: The study enrolled 70 patients with 40 patients undergoing laparoscopic transverse colectomy and 30 patients undergoing laparoscopic hemicolectomy. The intraoperative accidental hemorrhage and multiple organ resection occurred similarly in the two groups. In transverse colectomy, caudal-to-cephalic approach was likely to harvest more lymph nodes although require more operation time than cephalic-to-caudal approach (23.1±14.3 versus 13.4±5.4 lymph nodes, P=0.004; 184.3±37.1 min versus 146.3±44.4 min, P=0.012). The laparoscopic transverse colectomy was marginally associated with lower incidence of overall postoperative complications and shorter postoperative hospital stay although without statistical significance (8(20.0%) versus 12(40.0%), P=0.067; 7(5-12) VS 7(5-18), P=0.060). The 3-year DFS showed no significant difference (3-year DFS 89.7% in transverse colectomy versus 89.9% in hemicolectomy, P=0.688) between the two groups. The alternating consistency of defecation occurred significantly less after laparoscopic transverse colectomy than laparoscopic hemicolectomy (15(51.7%) VS 20(80.0%), P=0.030). Conclusion: The laparoscopic transverse colectomy is technically feasible with satisfactory oncological and functional outcomes for mid-transverse colon cancer. Performing the caudal-to-cephalic approach might be more advantageous in lymphadenectomy.